Unveiling LGBTQ+ Rights Movements in Pakistan: A Computational Sociology Inquiry through a Cultural Studies Lens - Saqib Raza; Mubashra Tayyaba; M. Hamza Naeem; Zaib un Nisa; Muhammad Ramzan; Mustafa Ali (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study examines a multidisciplinary approach of computational sociology, psychological study, communicational dimensions, and cultural studies led by the LGBTQ+ movement in Pakistan; this approach is investigated by Judith Butler's Queer theory. The theory is represented as a theoretical framework for analyzing the identity we have within us through the LGBTQ+ movement and the existing scenario in Pakistan. By using a socio-psychological context, qualitative research would be the lens through which to inspect various facets of LGBTQ+ activism accepted in Pakistan. Computational sociology and behavioral psychology are the methods used to represent satisfactory patterns and acceptable trends and enhance the structural network offline or through online speeches by activists. Text mining and sentimental analysis would be the technique, alongside network analysis of online communication of social media platforms, which would be used for identifying patterns, structural networks, and the trends adopted both online and offline. Simultaneously, the interpretation from cultural studies would shed light on how cultural norms represent LGBTQ+ people by traversing cultural identity through Butler's theory. The scenarios of remarking LGBTQ+ is a defined theory that elaborates that gender reality is performative: it is real only as well as performed, signified by socio-cultural studies influenced by psychological strategies. This research work emphasizes cultural awareness through socio-psychological aspects in Pakistan, examining conventional ideas and power politics about gender and identity, reagreeing LGBTQ+. The findings are amazing in that they have a great impact on the LGBTQ+ rights movements in Pakistan, with the implicated uses for advocacy as well as refined thoughts for theoretical contributions in academic discourse. Though the study provides clear findings, rather it is also important to register the limitations, such as the potential biases in self-reported data and the confined scope of social and behavioral adaptation in Pakistan. Future research should be expanded by advanced computational techniques to incorporate the development of intersectional approaches to LGBTQ+.